Help through demonstration and automation for interactive computing systems: a survey of recent works - Silva, J. L.; Rodrigues, P. (International Journal of Electrical and Computer Engineering, 2021)
Usability is very important however, it is still difficult to develop interactive computing systems that meet all user’s specificities. Help systems should be a way of bridging this gap. This paper presents a general survey on recent works (building upon previous surveys) related to improving applications’ help through demonstration and automation and, identifies which technologies are acting as enablers. The main contributions are, identifying (i) which are the recent existing solutions; (ii) which aspects must be investigated further; and (iii) which are the main difficulties that are preventing a faster progress.